2005
DOI: 10.1177/1077558705281060
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perceptions of Managed Care: A Review of the Literature

Abstract: In this article, the authors review the health services research literature regarding physician attitudes and opinions relating to managed care and how managed care has affected their clinical practice. This literature suggests that physician perceptions of managed care are largely related to the nature of their ties to managed care plans and to their selection of practice setting. There are substantial limitations in study designs and execution, suggesting that many of the published findings should be viewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
19
0
5
Order By: Relevance
“…12,16,21,22 The model was used in designing the survey instrument and guided empirical testing of models.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…12,16,21,22 The model was used in designing the survey instrument and guided empirical testing of models.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Investigaciones desarrolladas en sistemas de salud con modelos de competencia regulada muestran cómo elementos organizativos característicos de este modelo, como el uso de mecanismos de control de la atención por parte de las aseguradoras, influyen de forma determinante en el uso de los servicios (46,47).…”
Section: Discusión Y Conclusionesunclassified
“…Therefore, provider perceptions and willingness to participate are important factors in the success of [41]. A 2005 systematic review on provider attitudes regarding managed care found that physicians generally perceived that managed care had led to a loss of autonomy, increased administrative demands and practice overhead costs, and reduced time available for patient care [42]. However, it is important to note that the included studies were published from 1985 to 2002 and therefore primarily examined HMO models that predominated during that time.…”
Section: Provider Perceptionsmentioning
confidence: 99%